The intermediate-age open clusters Ruprecht 61, Czernik 32, NGC 2225 and 2262 - Carraro, G. (2005)
We present the first BVI CCD photometry to V = 22.0 of four fields centred on the region of the southern Galactic star clusters Ruprecht 61, Czernik 32, NGC 2225 and 2262 and of four displaced control fields. These clusters have never been studied before, and we provide for the first time estimates of their fundamental parameters, specifically radial extent, age, distance and reddening. We find that the four clusters are all of intermediate age (around 1 Gyr), close to the Sun and possess lower than solar metal abundance.